Corrosion behaviour of aluminium-graphene nano platelets (AL/GNP) nanocomposite / Subashiny Prabakaran - Subashiny, Prabakaran (2019)
This study was conducted to study the effect of adding graphene reinforcement to aluminium matrix, on the composite’s corrosion behavior. Aluminium-graphene nanoplatelet composites (Al/GNP) of different aluminium and graphene nanoplatelets composition percentages were produced. The corrosion behavior of Al-5%GNP, Al-10%GNP and Al-15%GNP composites was examined in solutions of three different corrosion molarity i.e. 1M, 3M and 5M of sodium chloride (NaCl) solutions, via Cyclic Potentiodynamic Polarization method. The electrochemical test was followed by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS) investigations, to compliment the test results. The study revealed that the presence of graphene and its increasing amount in the metal matrix composite (MMC), increases corrosion rate while decreasing the polarization resistance of aluminium. SEM/EDS examination of the corroded test materials indicated that the graphene in the MMC encouraged aluminium to corrode more, due to galvanic corrosion phenomenon. This effect was seen to be increasing when amount of graphene added was also increased.